Comparative Antimicrobial Activity of Silver Nanoparticles Synthesized by Corynebacterium glutamicum and Plant Extracts - Mohammad et al. (Baghdad Science Journal, 2019)
Biosynthesis of nanoparticles has received considerable attention due to the growing need to develop environmentally benign nanoparticle synthesis processes that do not use toxic chemicals. Therefore, biosynthetic methods employing both biological agents such as bacteria and fungus or plant extracts have emerged as a simple and a viable alternative to chemical synthetic and physical method .It is well known that many microbes produce an organic material either intracellular or extracellular which is playing important role in the remediation of toxic metals through reduction of metal ions and acting as interesting Nano factories. As a result, in the present study Ag NPs were synthesized by two methods biosynthetic technique using supernatant of Corynebacterium glutamicum that isolated from soil and green synthesis method by using plant extracts of fresh green plants.Ag NPs which synthesized by two methods were investigated visually by monitoring the color shift of reaction mixture from pale yellow to brown color, UV-Visible spectrophotometer was used to measure maximum absorbance of synthesized Ag NPs. The nanoparticles synthesized from Corynebacterium glutamicum exhibited maximum antimicrobial activity against selected pathogenic and environmental strains more than Ag NPs synthesized by green synthesis method from Spinacia oleracea, Malva parviflora and Eruca sativa. plant extracts